Sodium Ion Batteries: A Dual‐Insertion Type Sodium‐Ion Full Cell Based on High‐Quality Ternary‐Metal Prussian Blue Analogs (Adv. Energy Mater. 11/2018). Issue 11 (17th April 2018) - Peng, Jian; Wang, Jinsong; Yi, Haocong; Hu, WenJing; Yu, Yonghui; Yin, Jinwen; Shen, Yi; Liu, Yi; Luo, Jiahuan; Xu, Yue; Wei, Peng; Li, Yuyu; et al.
Abstract : In article number1702856, researchers from Huazhong University of Science and Technology, Jiantao Han and co‐workers, report the fabrication of a high rate and long life dual‐insertion sodium‐ion full cell that shows no noticeable capacity fading over 300 cycles. The fabrication utilizes high quality ternary‐metal Prussian blue analogues with large structural strain‐suppression. This technique could provide new avenues toward practical applications of sodium ion batteries for large‐scale energy storage systems.